Stadium games : fifty years of big league greed and bush league boondoggles - Weiner, Jay, 1954- (University of Minnesota Press, 2000)
In Stadium Games, veteran Minneapolis Star Tribune reporter Jay Weiner analyzes Minnesota's fifty-year history with pro sports and the issues contributing to the bid for a new stadium for the Minnesota Twins, along the way providing a big-picture evaluation of national sports economics.